Determinants of inflation in Poland: A structural cointegration approach - Byung-Yeon Kim (Bank of Finland, Institute for Economies in Transition (BOFIT), 2001)
Using cointegration and error-correction models, this paper analyses the relative impacts of the monetary, labour and foreign sectors on Polish inflation from 1990 to 1999.Following the development of a theoretical framework, we use a structural system approach in which cointegration relationships are used to derive deviations from steady-state levels.The deviations are interpreted as excess demand pressure on inflation in a given sector and subsequently incorporated in order to determine the short-run dynamics of Polish inflation.The results suggest that the labour and external sectors dominated the determination of Polish inflation during the above period, but their effects have been opposite since 1994.The appreciation of the domestic currency contributed to reducing inflation, while excessive wage increases prevented inflation from decreasing to a lower level.The monetary sector appears not to have exerted influence on inflation, suggesting monetary policy has been passive.
URN:NBN:fi:bof-201408071969
Keywords: 330